Embracing the F-Word Together: My Mom and Me Swearing by Feminism - Shroff, Farah Mahrukh` Coomi (Journal of the Motherhood Initiative for Research and Community Involvement, 2021)
Activism—a playful, joyful form of activism—has been a central feature of my life, partly because of the way in which my mom and I grew as activists together. Feminism, antiracism, and decolonial forms of activism are foundational in my scholarly work and my daily life. In this piece, I take a light-hearted approach to the ways in which my mom and I took up feminism. The Parsi community emanates from Persia and has been in South Asia for hundreds of years. In this narrative, I tell stories about my mom, Mahrookh, and me, as we learned about feminism together, on the West Coast of Turtle Island (North America). My mom grew up in India, the youngest with four brothers. Her dad, Nariman Munshi, was so keen to have a daughter that, despite my Granny’s insistence on having only two kids, they kept trying until they got a girl! So she was named Rani—Queen—and she was treated like a precious gift by her parents. Tragically, her father was murdered when she was only twelve years old, irrevocably disrupting everything, forever. Her brothers became tougher than her dad had ever been. When she received an invitation from her aunt in Nairobi, Kenya, to help take care of the family while Masi (mom’s sister) was convalescing from surgery, Mom jumped on the boat to escape. She had a lovely time in Nairobi and ended up married to Hoshang Shroff, my dad, within a few years, partly because her Masa (Masi’s husband) thought it’d be a great way to keep her in Nairobi. Marrying at age seventeen was far too early, and my Granny was furious! She slapped Masa with a whopping strike! My mom and me had a feminist Granny, who inspired us. Moving to the lands of the Coast Salish Nations, where this narrative begins, provided us with even more opportunities to evolve as feminists. (Please see the accompanying video, which forms part of this narrative: https://zxxresearch.med.ubc.ca/resources/.)